The Coptic-Orthodox Father Matta Al-Miskīn: An Introductory Approach to His Life, His Work and His Theology - Abdelmalak, Ashraf Nageh Ibrahim (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2023)
This article is intended to provide an answer to the following questions: Who was the Coptic-Orthodox father Matta Al-Miskīn (1919-2006) and what were his theories and his most important ideas? In order to offer a detailed answer to these questions, and to introduce succinctly the author who is considered —rightly— one of the Coptic-Orthodox theology leading representatives of the 20th century, same as one of key-figures of the Arab Christianity, today. The proposed structure has two main parts, an introduction and some final remarks. Firstly, a brief account of the life of the Coptic-Orthodox theologian is described, as well as a general presentation of his writings. Secondly, a synthesis of his spiritual, monastic-mystical, biblical, patristic and dogmatic-theological thought is proposed.